Bacteriological Quality of Drinking Water and Associated Factors at the Internally Displaced People Sites, Gedeo Zone, Southern Ethiopia: A Cross-sectional Study - Zemachu Ashuro; Mekonnen Birhanie Aregu; Girum Gebremeskel Kanno; Belay Negassa; Negasa Eshete Soboksa; Awash Alembo; Eshetu Ararsa; Fikru Badecha; Solomon Tassew (SAGE Publishing, 2021)
Background: Providing safe and adequate Water, Sanitation and Hygiene (WASH) services in response to emergencies is a major problem. Globally, few studies have investigated the bacteriological quality of drinking water at the IDP sites. Therefore, the objective of this study was to evaluate the bacteriological quality of drinking water and associated factors at the IDP sites of Gedeo zone. Methods: A cross-sectional study was conducted on 213 water samples collected from November to December 2018. The membrane filter technique was used to retain bacteria and lauryl sulphate broth media was used to detect faecal coliforms. After incubation of 14 hours at 44°C, faecal coliforms with yellow colonies were counted and expressed in terms of CFU/100 ml of water. The data were entered into Epi data version 3.1 and exported to STATA version 14 for analysis. Binary logistic regression analysis with 95%CI and P ⩽ .05 was used to identify factors associated with an outcome variable. Results: Out of 213 water samples collected, 107 (50.2%) samples were tested positive for faecal coliforms. The presence of latrines in uphill (AOR: 6.7, 95%CI: 1.0-42.9), other sources of pollution (AOR: 5.0, 95%CI: 1.1-22.3), inadequate fencing (AOR: 7.1, 95%CI: 1.3-40.2) and lack of diversion ditch (AOR: 6.3, 95%CI: 1.0-37.6) were factors significantly associated with faecal contamination of springs. Dug wells that had a latrine within 10 m (AOR: 11.4, 95%CI: 1.8-72.1), other pollution sources within 10 m (AOR: 7.9, 95%CI: 1.9-32.4), inadequate fencing (AOR: 2.8, 95%CI: 1.0-7.9), drawing water using a bucket with rope (AOR: 7.3, 95%CI: 1.6-33.4) and unsanitary well cover (AOR: 3.4, 95%CI: 1.1-10.4) were factors significantly associated with faecal contamination of wells. Conclusions: The majority of the water sources in internally displaced people sites were tested positive for faecal coliforms. The presence of latrine in uphill, other sources of pollution, inadequate fencing, lack of diversion ditch, drawing water using a bucket with rope and unsanitary well cover were factors associated with the presence of faecal coliforms. Therefore, adequate fencing, proper diversion ditch construction and hygiene promotion should be done to protect water sources from faecal contamination. Furthermore, latrines and other point sources of contamination should be located at least 10 m away or at a lower elevation from water sources.